(untitled) (CIENCIA Y TECNOLOGÍA AGROPECUARIA, 2021)
Biostimulants represent a practical alternative to increase crop yield and production. Therefore, the objective of this investigation was to assess the effect of thiamine on growth and development of paprika. The study was conducted from a positivist paradigm in a quantitative approach, a type of explanatory research and experimental field, considering a completely randomized statistical design, with thiamine applications in 10 cc per alveolar dose in sprouting trays with paprika seedlings at an 8-day frequency (T2); in addition, there were witness seedlings to which thiamin (T1) was not applied. The variables of growth and production in the paprika crop measured were: seedling emergency capacity (%), plant height (AP), number of fruits harvested (NFr), fruit diameter (DFr), fruit length (LFr), fruit weight (PFr). Statistically significant differences were observed in plants where thiamin was applied, where T2 had a positive effect on the emergency capacity of paprika seedlings, with 97,5% compared to T1 with a value of 77,5%. In addition, higher BP (141,80 cm) was presented in T2 compared to T1 (29,73 cm). The variables of growth and production were favored in T2: number of fruits harvested, diameter of the fruit, length of the fruit and weight of the fruit, where 7,66 was obtained in NFr; 13,28 cm for DFr; 22,06 cm of LFr and 310,44 g of PFr; with statistical differences of T1 with values of 4,26 in NFr; 6,64 cm for DFr; 7,93 cm in LFr and 68,67 g in PFr. Therefore, it is recommended to make applications of thiamin with this dose in the cultivation of paprika with soil and climate conditions similar to those of the study.